Total Electron Detachment and Induced Cationic Fragmentation Cross Sections for Superoxide Anion (O2−) Collisions with Benzene (C6H6) Molecules - Guerra, Carlos (2022)
Funding Information: Acknowledgments: This article is based upon work from COST action CA18212—Molecular Dynamics in the GAS phase (MD-GAS), supported by COST (European Cooperation in Science and Technology). The authors acknowledge the generous allocation of computer time at the Centro de Computación Científica at the Universidad Autónoma de Madrid (CCC-UAM). CG acknowledges funding from the IFHARU-SENACYT Program of Panamá through the Grant No. 270-2018-364. SK acknowledges the Portuguese National Funding Agency FCT through the and ERASMUS+ 29191(533)107/2019/SMT and PTDC/FIS-AQM/31281/2017. This work was also supported by the Radiation Biology and Biophysics Doctoral Training Programme (RaBBiT; Grant PD/00193/2012) Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.